An efficient public key based security architecture for wireless sensor networks - Haque, Md. Mokammel; Pathan, Al-Sakib Khan; Hong, Choong Seon (2007)
In this paper, we propose a public key based security architecture for Wireless Sensor Networks (WSNs). The basic architecture comprises of two schemes; a key handshaking scheme based on simple linear operations for fast computation and an identity based cryptosystem which does not require any certificate authority. Our analysis shows that, the combined scheme ensures a good level of security and is very much suitable for the energy constrained trend of wireless sensor network.